Greasing the wheels of international commerce: how services facilitate firms' international sourcing. (22nd February 2013) - Debaere, Peter; Görg, Holger; Raff, Horst
<x xml:space="preserve">Abstract</x> Abstract We use plant‐level data to study the link between the local availability of services and the decision of manufacturing firms to source materials from abroad. We develop a model to generate predictions about how the intensity of international sourcing of materials depends on the availability of services and firm characteristics. These predictions are supported by the data. Greater availability of services across regions, industries, and time increases firms' foreign sourcing of materials relative to sales. The impact of services differs by firm type. National firms' sourcing responds to changes in regional service conditions, whereas multinationals tend to be less affected.